Development and duration of BCG-induced allergy in the guinea-pig - Tolderlund, Knud (1960)
In assessing the biological activity of BCG vaccine by tuberculin testing of vaccinated guinea-pigs, it is necessary to take into account the rates of development and waning of allergy, and also the boosting effect on waning allergy caused by the tuberculin test itself. Using Danish liquid vaccine (in approximately standard dose), the authors have carried out two series of tests, involving more than six hundred guinea-pigs, to evaluate the significance of these factors. Post-vaccination tuberculin sensitivity was found to reach a maximum within 1-2 months. Three months after vaccination the BCG-induced allergy began to wane, and after 12 months it had dropped almost to the level observed in non-vaccinated guinea-pigs. The tuberculin test had a strong boosting effect, however, and even 12 months after vaccination the waning sensitivity could be considerably increased by a single injection of 10 TU of tuberculin. An analysis of the results showed that the waning of the level of allergy takes place gradually over several months. This is not an effect of aging, however, as the response to vaccination was found to be independent of the age of the animals. The indications of this study are that tuberculin testing of guinea-pigs used for the laboratory control of BCG vaccine is best performed about 6 weeks after vaccination.